The Covid-19 Pandemic and the Students’ Limited Digital Competence in Writing Scientific Papers - Rosa, Silvia; Bahri, Susila; Suryani, Nilma; Yustina, Luli Sari (KnE Social Sciences, 2023)
This study aims to explore the correlation between students’ digital competence and indecision with the challenges they encounter during the online scientific writing assistance process amid the Covid-19 pandemic. Students faced multiple forms of hesitation, communication breakdowns, and missed opportunities for discussion during this process. The research findings target guidelines for writing scientific papers. Qualitative data was collected through an online survey of 100 students from public universities in Indonesia. The research instrument employed an online questionnaire distributed to students via the Google Forms application. Data analysis was conducted using qualitative and interpretive approaches based on the principles of content analysis. The results revealed that students experienced profound doubts and confusion when it came to organizing their thoughts while conducting research and writing scientific papers as final projects. This research suggests that students’ digital intelligence alone is insufficient for accessing the information required by their intellectual intelligence in writing scientific papers. Keywords: digital competence, scientific papers, Covid-19 pandemic